Students’ reasons for being reluctant to seek help for mental health concerns in secondary schools - Karen A. Patte; Katelyn Battista; Jessica Goddard; Jordana Ferro; Scott T. Leatherdale (Cogent Mental Health)
Understanding adolescents’ reasons for being reluctant to seek mental health help is important to improve early identification, for which schools represent important contexts. Subgroups may have unique reasons, thus requiring different strategies to overcome reluctance. Latent class analysis was conducted to identify classes of females and males based on their reasons for being reluctant to seek help from school adults. We used cross-sectional survey data collected in 2018–2019 from 70,794 students attending 136 Canadian secondary schools. The most frequently reported reason was preferring to handle problems themselves. Five-class solutions resulted, with four similar classes in males and females: “low reluctance”, “go alone”, “stigma”, and a class with high probabilities for all provided reasons. A “wouldn’t know who” (to approach) class in females and a “no one I would feel comfortable talking to” class in males also resulted. Students with depression and anxiety had higher odds of belonging to all reluctant classes relative to the low reluctance class. Help seeking reluctancy in school contexts remains common, particularly among students that may be most in need of support. Many adolescents that prefer to handle problems themselves have concerns about confidentiality and perceptions that school adults would not be able to help.